Attentional Prioritization of Complex, Naturalistic Stimuli Maintained in Working-Memory–A Dot-Probe Event-Related Potentials Study - Rutkowska, Natalia; Doradzińska, Łucja; Bola, Michał (Frontiers in Human Neuroscience, 2022)
Recent studies suggest that a stimulus actively maintained in working memory (WM) automatically captures visual attention when subsequently perceived. Such a WM-based guidance effect has been consistently observed for stimuli defined by simple features, such as color or orientation, but studies using more complex stimuli provided inconclusive results. Therefore, we investigated whether the WM-based guidance effect occurs also for naturalistic stimuli, whose identity is defined by multiple features and relations among them, specifically for faces and houses. The experiment consisted of multiple blocks in which participants (N = 28) either memorized or merely saw (WM or exposure condition, respectively) a template stimulus and then performed several dot-probe trials, with pairs of stimuli (template and control) presented laterally as distractors and followed by a target-asterisk. Analysis of reaction-times (RT) in the dot-probe task shows that memorized stimuli were prioritized by attention and points towards attention-hold, rather than capture, as a mechanism of attentional prioritization. Consistent with this interpretation, memorized items did not evoke a lateralized N2pc ERP component, thought to indicate attention shifts. However, in an exploratory ERP analysis we found evidence for a very early (100-200 ms post-stimulus) prioritization specific to the memorized faces, which is in line with the sensory recruitment theory of WM. In conclusion, our data provide evidence that complex stimuli are prioritized by attention when maintained in WM, and that the mechanism of such prioritization is based on a prolonged hold of spatial attention.